2018
DOI: 10.1128/mbio.01005-18
|View full text |Cite
|
Sign up to set email alerts
|

Erratum for Diago-Navarro et al., “Novel, Broadly Reactive Anticapsular Antibodies against Carbapenem-Resistant Klebsiella pneumoniae Protect from Infection”

Abstract: After careful review of the legend of Fig. 3, we realized that there was an error in the section describing panel A. The revised legend for Fig. 3A should read "Neutrophil phagocytosis of CR K. pneumoniae strain 39 cells was increased after incubation with 8F12 and 17H12 in the presence of NHS or HI-NHS." We also noticed that on PDF page 5 (first paragraph), the statement about neutrophil killing should reference Fig. 3B, not Fig. 3D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Although we sought to generate all three additional subclasses, only mIgG 1 and mIgG 2a variants were discovered in our initial screen, and only mIgG 1 variants could be enriched by downstream sib selection. The mIgG 1 hybridomas were verified to exclusively produce mIgG 1 , and the sequence of the variable region of the new clone was found to be identical to that of the mIgG 3 parent (the characteristics of which have been previously published [14]).…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…Although we sought to generate all three additional subclasses, only mIgG 1 and mIgG 2a variants were discovered in our initial screen, and only mIgG 1 variants could be enriched by downstream sib selection. The mIgG 1 hybridomas were verified to exclusively produce mIgG 1 , and the sequence of the variable region of the new clone was found to be identical to that of the mIgG 3 parent (the characteristics of which have been previously published [14]).…”
Section: Resultsmentioning
confidence: 74%
“…To investigate how subclass switching affected binding, we compared the affinity of the new mIgG 1 to that of its parent mIgG 3 against the wzi154 CPS originally used to generate the MAb (14). Analysis by enzyme-limited immunosorbent assay (ELISA) showed the mIgG 1 to have 4-fold less binding than its mIgG 3 counterpart, with 50% effective concentration (EC 50 ) values of 27.6 nM (95% confidence interval [CI], 18.8 to 40.6 nM) and 6.81 nM (95% CI, 3.00 to 13.2 nM), respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, Seeberger et al recently described a semisynthetic glycoconjugate vaccine based on the structure of CPS from K. pneumoniae carbapenemase (KPC)-containing isolates conjugated to the diphtheria toxoid carrier CRM197 (35). Moreover, Diago-Navarro et al demonstrated that treatment of mice with MAbs specific for a CPS glycoconjugate caused a reduction in the number of K. pneumoniae recovered from lungs, liver, and spleen of infected mice (36). Although the glycoconjugate successfully elicited CPSspecific antibody in mice and rabbits, the ability of the vaccine to protect against K. pneumoniae was not tested owing to the lack of an appropriate infection model for KPC strains that sufficiently approximates host comorbidities.…”
Section: Discussionmentioning
confidence: 99%